Extraction and characterization of natural fiber from Eleusine indica grass as reinforcement of sustainable fiber reinforced polymer composites. Issue 11 (2nd November 2021) - Khan, Anish; Vijay, R; Singaravelu, D Lenin; Sanjay, M R; Siengchin, Suchart; Verpoort, Francis; Alamry, Khalid A.; Asiri, Abdullah M
ABSTRACT: In the present scenario, the searching for novel plant fibers able to be used as reinforcement of polymer composites is highly appreciable. This study deals with extraction and characterization of Eleusine indica grass fibers extracted from its stem by manual retting process. From this study, it was found that the Eleusine indica has higher cellulose of 61.3 wt% content, density of 1143 kg/m 3, average tensile strength and Young's modulus equal to 22 MPa and 10.75 GPa, respectively. From the XRD studies, it was noted that the Crystallinity Index (CI) of Eleusine indica was 45%. The surface morphology of Eleusine indica grass was examined using a Scanning Electron Microscope (SEM) and Chemical functional group were confirmed by Fourier transform infrared spectroscopy (FT-IR). The thermal stability of EIF was evaluated using TG and DTG curves from Thermogravimetric (TG) analysis. The characterization results confirmed that Eleusine indica grass could be used for the production of sustainable fiber-reinforced polymer composites.